Emotional Stress Relief Mechanism of English Translation Practitioners Based on Role Cognition - Wei Hu; Yipeng Luo (Hindawi-Wiley, 2022)
The emotional stress of English translation practitioners is an important research content of psychological organization counseling behavior. Based on the theory of role cognition, this paper adopts the perspective of emotional stress experience, integrates the construction theory and the self-determination theory, and builds an emotional stress relief mechanism for English translation practitioners. On the basis of sorting out psychological capital, emotional commitment, and behavioral variables of organizational practitioners, the article summarizes the concept, dimension, measurement, and causes and effects of variables and solves the problem of quantitative analysis of emotional stress. In the simulation process, the role cognitive variables and local cognitive variables are extracted separately using the dual-branch mitigation mechanism structure to enhance the diversity of the extracted cognitive variables; in the local branch, a loss function of emotional stress overlapping partial penalty mechanism is constructed. This mechanism is used to select a suitable destination sink node for the sensor nodes around the sink node with heavy load to transmit data and effectively relieve the data collection pressure of the original sink node. The experimental results show that by using role cognitive variables and local cognitive variables in the training of classification loss and triple loss, respectively, the mitigation mechanism can mine subtle and significant cognitive variables from the local area and finally integrate role cognitive cognition. The accuracy rate of obtaining 297 questionnaires reached 91.4%, which effectively promoted the mechanism research of emotional stress on the behavior of English translation practitioners.